Acoustic modeling of the singing vortex and its sound signatures. (February 2018) - Song, Mingtai; Xu, Lianghao; Peng, Xiaoxing; Tang, Denghai; Chen, Yihong
Highlights: The special phenomenon of singing vortex was successfully reproduced. Singing vortex is shown to be periodical in time and standing-wave-like in space. We propose an acoustic model to demonstrate the sound signatures of singing vortex. The theoretical model qualitatively agrees with the experimental data. Singing frequency varies linearly with velocity and inversely with attack angle. Abstract: The "singing vortex" is a special phenomenon generated from a cavitating vortex trailing from the tip of an elliptical hydrofoil under certain conditions. In this paper, the special phenomenon was successfully reproduced similarly to that fromMaines and Arndt (1997) . The "singing vortex" presents a periodical characteristic in the time domain and a standing wave pattern in the spatial domain, while multiple distinct peaks show up in the sound spectrum. An acoustic model aiming to demonstrate the sound signatures of the singing vortex was proposed. The theoretical model provided a reasonable estimation of the sound radiation intensity compared to the experimental data. The relationship between the "singing" frequency and flow parameters was also investigated attempting to explain the mechanism of the singing vortex.